SCIENCE COMMUNICATION AND THE ANIME DUNGEON MESHI: THE USE OF AUDIOVISUAL MEDIA IN SCIENCE EDUCATION (REMUNOM, 2025)
The objective of this study is to analyze the content present in the work Dungeon Meshi and discuss the references to scientific concepts and science observed in the animation, evaluating its pedagogical potential as a tool for science communication. A qualitative study was conducted on the animation, documenting the moments in which scientific terms were mentioned, either through a character's speech or visually. These data were extracted and organized into a table according to the content, to be discussed with the references. In total, 18 excerpts were taken from the episodes, containing plot events that addressed the following topics: Ecology (5), Scientific Methodology (3), Cellular Biology (3), Taxonomy (2), Zoology (2), and Biotechnology (1). Therefore, it is concluded that the analyzed work presents a range of scientific concepts in its plot, which can be connected to the curriculum taught in the classroom and, as such, serve as a teaching resource. However, it is important to consider that, even though it is potentially a revolutionary technology for education, the technology itself should not overshadow the specific content.